The role of Fabry–Perot resonance for a periodic array of gold nano-slits. Issue 11 (16th June 2016) - Zhang, Siwen; Sun, Xiaodong; Wu, Feng; Yang, Jianing
Abstract: Comprehensive investigations of electromagnetic enhancement and transmittance by a periodic array of gold nano-slits are presented. Rigorous numerical data can be well predicted by a simple Fabry–Perot model. By virtue of the model, the role of Fabry–Perot resonance that enables giant electromagnetic enhancement and high transmittance by a gold nano-slit array is studied. Distinct impacts of array period and slit width on electromagnetic enhancement and those on transmittance are explored. Numerical results imply that contributions of electromagnetic enhancement and transmittance should be considered together in determining the actual enhanced effect of sample signals in surface-enhanced Raman scattering application.